The nutritional requirements of Haliotis midae and development of a practical diet for abalone aquaculture - Britz, Peter Jacobus (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1996)
The available literature on abalone nutrition was synthesised and the prospects for developing a complete pelleted dry feed for Haliotis midae evaluated. The similar body compositions, digestive structures, enzyme activity, acceptance of a wide variety of feed ingredients and comparable growth performance on formulated diets of various abalone species suggests that they have similar nutritional requirements. Abalone also appear to be similar to other farmed monogastric animals in that digestion is primarily extracelluar and they possess a large, muscular crop and stomach. Abalone energy metabolism is carbohydrate based. They are capable of digesting high levels of dietary protein but their ability to utilise fat is limited. Abalone have been shown to consume predictable amounts of dry feed which is efficiently converted into body weight. Efficiency indices of utilisation of formulated feeds, such as feed conversion ratio, protein efficiency ratio, net protein utilisation and apparent digestibility have been successfully applied to abalone. It was concluded that the prospects for developing complete diets for H. midae using a conventional animal feed science model were good. The ability of H. midae to utilise a range of proteins which had potential for inclusion in practical diets was investigated. Five protein rich ingredients, namely, casein, fishmeal, soya oil cake, Spirulina, and torula yeast, were fed to H. midae in semi-purified diets. Two algal diets, fresh Plocamium corallorhiza and dried Ecklonia maxima were fed as controls. Abalone fed on fishmeal and Spirulina based diets displayed significantly higher growth rates than diets containing soya oil cake, torula yeast, casein and E. maxima. Growth rates of abalone fed with P. corallorhiza were significantly lower than all other diets. All artificial diets yield lower feed conversion ratios (0.7-1.8) and higher protein efficiency ratios (3.3-6.5) ratios than the seaweed control diets (FCR = 2.8-3.4; PER = 2.2-3.0). The results indicated that fishmeal and Spirulina were the most suitable proteins for inclusion in practical diets for H. midae. The effect of protein level on growth rate and nutritional indices was evaluated by feeding starch bound, fishmeal based diets containing 27, 32, 37, 42 and 47% protein to juvenile H. midae. Weight gain was positively related to the level of dietary protein, increasing by 18% between 27% and 47% protein. Protein efficiency ratio declining from 3.2 to 2.3 with an increasing dietary protein content. Feed consumption rate was approximately 1% of body weight per day for all diets. Post-weaning abalone (ca. lOmm shell length, 0.2g) differed from larger juveniles (ca. 35mm, 8g) in their response to varying proportions of dietary protein and energy. The smaller animals appeared to have a lower protein requirement and poorer ability to utilise lipid than the larger juveniles. Proximate analyses revealed that the levels of protein, lipid and carbohydrate in abalone soft tissue increased with increasing dietary levels of these nutrients. Larger juveniles contained significantly higher levels of protein and carbohydrate, but lower levels of lipid, ash and moisture, than the smaller post-weaning abalone. The assimilation efficiency of [U-Â¹â ´C]-arginine by H. midae fed diets enriched with [U-Â¹â ´C]-arginine was only 0.45%. Furthennore, supplementation of diets with graded levels of crystalline arginine did not have any effect on growth rates. It was concluded that the prospects for defining the quantitative amino acid requirements of H. midae using crystalline amino acids are not promising. Rates of gastric evacuation and enzyme secretion were monitored in juvenile H. midae fed an extruded, fishmeal based dry feed. Gut fullness peaked 6h after feed was offered and the bulk of feed consumed was digested within 24 h. Enzyme secretion appeared to begin with the onset of feeding and continued for at least 6h after peak gut fullness was attained. Protease activity increased significantly following ingestion but amylase activity was maintained at a more or less constant level. A low level of lipase activity was observed suggesting that the ability of H. midae to digest fat is limited. The growth rate of H. midae fed an extruded, fishmeal based feed increased with increasing temperature between 12Â°C and 20Â°C. Between 20Â°C and 24Â°C a marked decline in growth rate accompanied by a deterioration in feed conversion and increased mortality was observed. Consumption of a dry pelleted feed was shown to be a function of body size and temperature. Based on these data a model which predicts a daily ration for H. midae was developed. The present study showed that H. midae efficiently utilises extruded dry feeds containing conventional feed ingredients. Although technical difficulties were encountered in measuring apparent digestibility, it was concluded that the prospects for developing practical diets according to established nutritional principles are promising.
Keywords: Abalones -- Nutrition; Abalone culture